(untitled) (Plant Tissue Culture and Biotechnology, 2026)
A highly efficient and repeatable in vitro protocol has been developed for rapid and mass scale propagation of Physalis minima L. Fresh nodal segments from field grown plants were aseptically cultured on MS medium alone or in combination with different PGRs. The nodal segments showed direct organogenesis and produced the highest number of multiple shoot buds (MSBs) (4.87 ± 0.12) per explant when cultured on MS medium supplemented with 2.0 mg/l BAP + 0.5 mg/l NAA. Nodal and leaf segments from in vitro grown shoots were further cultured on MS medium containing different concentrations and combinations of PGRs. Among the different combinations, MS + 2.0 mg/l BAP + 1.0 mg/l IAA was found to be the best for induction of maximum number of shoot buds (4.13 ± 0.11) per nodal explant with the highest percentage (95%) of shoot bud formation within 15-18 days of culture. Nodal segments proved to be better than leaf explants for callus induction. Maximum 86% of nodal segments produced brownish compact calli on MS medium fortified with 1.0 mg/l 2, 4-D + 0.5 mg/l Kn. It was noticed that the brownish friable calli did not undergo any kind of differentiation. The highest increase in length (cm) of shoot bud (3.60 ± 0.11cm) was noted on MS medium augmented with 1.0 mg/l BAP + 0.5 mg/l NAA. The elongated multiple shoot buds were individually transferred to rooting media. Maximum numbers of roots (5.87 ± 0.17) per micro shoot was recorded in half-strength MS medium supplemented with 1.0 mg/l IBA. The stout rooted plantlets were hardened in pots at 75% survival rate. Both micro propagated plants were stable and showed uniform morphological and growth characteristic following their establishment. Plant Tissue Cult. & Biotech. 35(2): 361-369, 2025 (December)